Cumplimiento tributario de la empresa KRADAC CIA LTDA, de la ciudad de Loja, periodo 2022. - Paccha Rojas, Karen Lizbeth (2024)
For the present work, it was necessary to review the literature, consolidating theoretical, technical and legal knowledge on the subject and a theoretical framework that allowed compliance with the established objectives; the type of taxpayer was identified, the regime to which it belongs, and the economic activity to which it is dedicated, through the observation and review of RUC, auxiliary reports and accounting records, in order to compare the current legal regulations and what they execute internally in the company. Once the necessary information was received, comparative tables of figures and data were designed to identify the differences detected during the evaluation under review during the period 2022. In the process, differences were established in the dates of presentation and values in each of the tax obligations, resulting in a delay in certain months in the delivery of VAT and ATS information, generating fines to the company in the amount of $410. In addition, differences are detailed that support the substitutions presented in the VAT return and the variation of values reported, of the ATS, VAT return, RDEP annex and accounting system, many of them are attributed to system configurations but others were determined to be cross-referencing of information not approved by those responsible for the accounting department. At the conclusion of this review, a report on the company's tax compliance was prepared, which consists of conclusions and recommendations on the results obtained, considering that it assesses the efficiency, timeliness, accuracy, and effectiveness of the tax procedures applied by the company, which is of interest to the company's managers, and to achieve better control in the fulfillment of its tax obligations.